"She Sounds Like a Small Child or Perhaps She has Problems"—Peers' Descriptions of Speech in 7-Year-Olds Born With Cleft Palate. (June 2020) - Nyberg, Jill; Hagberg, Emilie; Havstam, Christina
Objective: The aim of this study was to explore how 7-year-olds describe speech in children born with cleft palate in their own words and to investigate whether they perceive signs of velopharyngeal incompetence (VPI) and articulation errors, and if so, which terminology they use. Methods/Participants: Twenty 7-year-olds participated in 6 focus group interviews where they listened to 8 speech samples with different types of cleft speech characteristics and described what they heard. The same speech samples had been assessed by speech-language pathologists and comprised normal speech, different degrees of VPI, oral articulation disorders, and glottal articulation. The interviews were analyzed with qualitative content analysis. Results: The analysis resulted in 4 interlinked categories: descriptions of speech, thoughts on personal traits, consequences for communication, and emotional reactions and associations. Each category contains 4 to 5 subcategories with the children's descriptions and reflections. Glottal articulation and severe signs of VPI caused the most negative emotional reactions and were described as sounding scary and incomprehensible and the children speculated on the risk of social rejection of the speakers. Retracted oral articulation was also noted and described but with a vocabulary similar to the professionals. Minor signs of VPI were not noted. Conclusions: Seven-year-olds are direct and straightforward in their reactions to cleft palate speech characteristics. More pronounced signs of VPI and articulatory difficulties, also minor ones, are noted. Clinically, articulatory impairments may be more important to treat than minor signs of VPI.